Prevalencia de parásitos gastrointestinales en equinos durante el periodo invernal en la provincia de El Oro. - Sanchez Alvarado, Nicolas Andres (Machala : Universidad Técnica de Machala, 2024)
In the province of El Oro, the equine population has significantly increased, reflecting its socioeconomic importance. However, information on the prevalence and frequency of parasitic infections in horses is scarce, negatively affecting their performance and physical condition. Nematodes are a significant factor in disease and decreased performance in equines, highlighting the need for effective control of gastrointestinal helminths. The primary objective of this research was to determine the prevalence of gastrointestinal parasites in equines in the province of El Oro through parasitic sensitivity diagnostic tests. Various techniques were used to analyze fecal samples, with the most relevant being the Faust technique, which recorded 38.6%, and the Richie technique, with 37.10%. These data indicate the need to consider the analysis techniques and their effectiveness in detecting parasites. The two most predominant parasites identified in the study were *Strongylus* and *Oxyurus equi*, which are associated with greater positive impacts. These results underscore the necessity of developing more effective deworming programs tailored to the specific environmental conditions of the region to improve the health and performance of horses. Furthermore, they emphasize the importance of continuous monitoring and the application of precise diagnostic methods for the sustainable management of the equine population in El Oro.
En la provincia de El Oro, la población equina ha aumentado considerablemente, reflejando su importancia socioeconómica. Sin embargo, la información sobre la prevalencia y frecuencia de infecciones parasitarias en caballos es escasa, afectando negativamente su rendimiento y condición física. Los nematodos son un factor significativo de enfermedad y disminución del desempeño en equinos, destacando la necesidad de implementar un control efectivo de helmintos gastrointestinales. La presente investigación tuvo como objetivo principal determinar la prevalencia de parásitos gastrointestinales en equinos de la provincia de El Oro mediante pruebas de diagnóstico de sensibilidad parasitaria. Se utilizaron varias técnicas de análisis de muestras fecales, siendo las más relevantes la técnica de Faust, que registró un 38.6%, y la técnica de Richie, con un 37.10%. Estos datos indican la necesidad de considerar las técnicas de análisis y su efectividad en la detección de parásitos. Los dos parásitos más predominantes identificados en el estudio fueron Strongylus y Oxyurus Equi, los cuales se asocian con mayores impactos positivos. Estos resultados subrayan la necesidad de desarrollar programas de desparasitación más eficaces y adaptados a las condiciones ambientales específicas de la región, con el fin de mejorar la salud y el rendimiento de los caballos. Además, resaltan la importancia de la vigilancia continua y la aplicación de métodos de diagnóstico precisos para el manejo sostenible de la población equina en El Oro.
Keywords: PREVALENCIA; EQUINOS; PARASITOS; FAUST